A psicologia clínica e o mal-estar contemporâneo: impasses e re-significações - Barreto, Carmem Lúcia Brito Tavares (2002)
Departing from clinical experience, this study aims to comprehend the contemporary uneasiness. It shows the author's true testimony not only as a researcher, but also as a psychotherapist and supervisor. This research is based on disruptive clinical experiences by taking into account, as object for theoretical reflection, within the Person-Centered Approach, the Client-Centered Therapy. It makes a critical overview of the Client-Centered Therapy theory by analyzing Carl Rogers' concept of science as well as his conceptual path. Such analysis points to an insufficiency of the Actualizing Tendency and Anguish concepts toward sheltering and, at the same time, to promote a passage for the contemporary uneasiness. Thus, it indicates the need of another way to access and comprehend the fundamental and original human condition. Finally, this study presents Heidegger's anguish concept as a possible contribution to fertilize and re-signify the clinical praxis. As a result of such path, the author reveals her transitional moment of theoretical reflection, directing herself toward a psychological conception of clinic as "care" (Sorge), linked to a human existence theory conceived as an ethics of finitude acceptance, of transivity and conflicts. Such a theory demands a clinical praxis by conceiving a creation act as an opening to shelter something unknown, plenty of availability to carry forward onweself towards the "being-there” complexity. The author manifests that, in spite to have found some possible answers to her dislodged inquietude experience that motivated this actual work, its approached thematic, by its own complexity and dynamic involved, implies in an always present openness that instigate new sights and reflections, thus deserving further re-readings.